A Smart Port–City Integration Framework for Sustainable and Climate-Resilient Coastal Infrastructure - R.Herlan Guntoro; Giovanni Battista Puteri; Aditya Rinaldi; Yayu Nopriani Martha; Aji Permana (Momentum International Journal of Civil Engineering (MIJCE), 2026)
Coastal port cities face unprecedented challenges from climate change, urbanization pressures, and maritime traffic intensification, threatening both urban sustainability and maritime operational efficiency. This research develops a comprehensive Smart Port-City Integration Framework employing GIS-based spatial analysis and predictive modeling to address sea-level rise adaptation, traffic congestion mitigation, and land-use optimization. Through qualitative analysis incorporating perspectives from urban planning experts, maritime infrastructure specialists, and port authority administrators, this study identifies critical integration strategies balancing environmental resilience with economic vitality. The framework synthesizes civil engineering principles with sustainable urban planning methodologies, demonstrating how coastal cities can transform port-urban interfaces into climate-adaptive, economically productive, and socially equitable spaces. Findings reveal significant gaps in current planning approaches, particularly regarding climate risk assessment integration and stakeholder coordination mechanisms. The research contributes practical implementation pathways for port cities globally, offering evidence-based strategies for sustainable coastal development aligned with SDG 11 (Sustainable Cities) and SDG 13 (Climate Action), while enhancing maritime competitiveness through intelligent infrastructure design and resilient spatial planning frameworks.